2019
DOI: 10.1007/jhep07(2019)060
|View full text |Cite
|
Sign up to set email alerts
|

Production of purely gravitational dark matter: the case of fermion and vector boson

Abstract: We consider the simplest possibility for a model of particle dark matter in which dark matter has only gravitational interaction with the standard model sector. Even in such a case, it is known that the gravitational particle production in an expanding universe may lead to a correct relic abundance depending on the inflation scale and the mass of dark matter particle. We provide a comprehensive and systematic analysis of the gravitational particle production of fermionic and vectorial dark matter, and emphasiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(163 citation statements)
references
References 70 publications
2
161
0
Order By: Relevance
“…Given the correspondence between transverse vector fluctuations and scalar ones, it is expected that the energy density stored in small scale fluctuations can also be important here. In addition to that and as a particularity of the vector case, the authors of [42] (see [72] as well) showed that longitudinal vector fluctuations can be copiously produced during inflation also for κ = 0.…”
Section: Energy Density In Fluctuationsmentioning
confidence: 86%
“…Given the correspondence between transverse vector fluctuations and scalar ones, it is expected that the energy density stored in small scale fluctuations can also be important here. In addition to that and as a particularity of the vector case, the authors of [42] (see [72] as well) showed that longitudinal vector fluctuations can be copiously produced during inflation also for κ = 0.…”
Section: Energy Density In Fluctuationsmentioning
confidence: 86%
“…Furthermore, as shown in Refs. [38][39][40][41][42][43][44][45], oscillations of background quantities induced by inflaton dynamics can also contribute to particle production in the early universe.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38], spin-1/2 particles by refs. [39][40][41], spin-1 particles by refs. [40,[42][43][44], and spin-3/2 particles by refs.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41], spin-1 particles by refs. [40,[42][43][44], and spin-3/2 particles by refs. [31,45,46].…”
Section: Introductionmentioning
confidence: 99%